Hedonism on the behavior of consumer society as a global cultural transformation - Subawa, Nyoman Sri; Widhiasthini, Ni Wayan; Pika, Putu Ayu Titha Paramita; Suryawati, Putu Indah (International research journal of management, IT and social sciences, 2020)
This study deals with changes in consumer behavior based on hedonic desires. The change from consumption to consumerism. This is done on the purchase of four-wheeled vehicles (cars). This research is expected to provide awareness and critical understanding to the public to buy products according to their abilities, not get caught in the capitalist trap. This study uses descriptive qualitative and interpretive, by involving consumers, car marketers, and financial agents as informants. The results show that there has been a transformation in the behavior of consumer societies based on the desire of hedonism that is influenced by global cultural imperialism, such as instant culture and consumerism behavior. Further research needs to be done on consumers in excessive consumption of other products.